STRATEGI PENINGKATAN PROFESIONALISME GURU DALAM MEWUJUDKAN PEMBELAJARAN YANG INOVATIF DAN EFEKTIF DI SMA NEGERI 8 MEDAN - Sitorus, Elfany Julia Safitri; Aulia, Rizky; Saragih, Nopita Sari; Lubis, Jasmine Arafah (Yayasan Amanah Nur Aman, 2025)
The purpose of this study is to find and analyze methods to improve teachers' professionalism to create innovative and effective learning at SMA Negeri 8 Medan. This research uses a qualitative descriptive approach, which involves collecting data through observation, interviews, and documentation from teachers and students. The results show that teachers at SMA Negeri 8 Medan have done many things to become more professional, such as attending training and workshops, and using technology in learning. To increase students' participation and encouragement, teachers use diverse and interactive learning approaches. Teachers' professional development is also assisted by school facilities, policies and training. However, there are some problems found in this study, such as technology limitations, time, and adaptation to changes in learning methods. Overall, the methodology used has improved the quality of learning, as shown by increased student enthusiasm and understanding. This research recommends collaboration between teachers and school authorities, improved supporting facilities, and continuous training programs to create a more creative and successful learning environment.